Reasons for Contraceptive Nonuse among Women Having Unmet Need for Contraception in Developing Countries. Issue 2 (14th June 2014) - Sedgh, Gilda; Hussain, Rubina
Abstract : The level of unmet need for contraception—an important motivator of international family planning programs and policies—has declined only slightly in recent decades. This study draws upon data from 51 surveys conducted between 2006 and 2013 in Africa, Asia, and Latin America and the Caribbean to provide an updated review of the reasons why many married women having unmet need are not practicing contraception. We examine the reasons for contraceptive nonuse and how these reasons vary across countries and according to national levels of unmet need and contraceptive use. We present specific findings regarding the most widespread reasons for nonuse, particularly infrequent sex and concerns regarding side effects or health risks. Our findings suggest that access to services that provide a range of methods from which to choose, and information and counseling to help women select and effectively use an appropriate method, can be critical in helping women having unmet need overcome obstacles to contraceptive use.